2016
DOI: 10.1038/srep31520
|View full text |Cite
|
Sign up to set email alerts
|

Identification of salivary metabolomic biomarkers for oral cancer screening

Abstract: The objective of this study was to explore salivary metabolite biomarkers by profiling both saliva and tumor tissue samples for oral cancer screening. Paired tumor and control tissues were obtained from oral cancer patients and whole unstimulated saliva samples were collected from patients and healthy controls. The comprehensive metabolomic analysis for profiling hydrophilic metabolites was conducted using capillary electrophoresis time-of-flight mass spectrometry. In total, 85 and 45 metabolites showed signif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
156
1
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 170 publications
(161 citation statements)
references
References 49 publications
2
156
1
2
Order By: Relevance
“…Saliva represents another non‐invasive biological fluid and biomarker discovery was performed for oral and pancreatic cancer. Metabolomic profiling of cerebrospinal fluid (CSF) was performed to identify biomarkers for Alzheimer's disease .…”
Section: Analytical Applicationsmentioning
confidence: 99%
“…Saliva represents another non‐invasive biological fluid and biomarker discovery was performed for oral and pancreatic cancer. Metabolomic profiling of cerebrospinal fluid (CSF) was performed to identify biomarkers for Alzheimer's disease .…”
Section: Analytical Applicationsmentioning
confidence: 99%
“…Elevation in D-2-HG levels inhibits α-ketoglutarate-dependent enzymes and causes hypermethylation of histones and DNA, which results in altered gene expression, resulting in activation of oncogenes and inactivation of tumour-suppressor genes 75 76. Thus, D-2-HG levels could be helpful in the diagnosis of malignant brain tumours 76. One study showed elevated D-2-HG levels in the CSF of patients with IDH - mutant gliomas 94.…”
Section: Metabolomicsmentioning
confidence: 99%
“…Ishikawa et al. used a sheath‐liquid CE‐MS approach to find potential metabolic biomarkers for oral cancer screening in saliva and tumor tissue samples . Tumor and control tissues were obtained from oral cancer patients and saliva samples were collected from patients and healthy controls.…”
Section: Applicationsmentioning
confidence: 99%